2007
DOI: 10.1161/strokeaha.107.487918
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Carotid Adventitial Vasa Vasorum and Plaque Vascularization With Ultrasound Cadence Contrast Pulse Sequencing Technique and Echo-Contrast Agent

Abstract: Background and Purpose-Adventitial vasa vasorum and plaque vascularization have been established as predictors of unstable atheromasic lesions in cerebro-and cardiovascular patients. Ultrasound contrast agents provide reliable information on tissue perfusion and microcirculation. We used contrast ultrasound duplex scanning to identify carotid plaque vascularization. Methods-Contrast carotid duplex scanning was performed in 23 patients with plaques of different degree of stenosis and echogenicity. Results-Plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 12 publications
5
80
1
7
Order By: Relevance
“…Contrast-Enhanced Ultrasound CEUS represents a simple and noninvasive technique for the evaluation of plaque vascularization, allowing for the detection of plaque vasa vasorum that are abundant in vulnerable plaques [86][87][88].…”
Section: Contrast Enhancement (Us-mri-ct)mentioning
confidence: 99%
“…Contrast-Enhanced Ultrasound CEUS represents a simple and noninvasive technique for the evaluation of plaque vascularization, allowing for the detection of plaque vasa vasorum that are abundant in vulnerable plaques [86][87][88].…”
Section: Contrast Enhancement (Us-mri-ct)mentioning
confidence: 99%
“…They also observed the neovascularization regression after 8 months of statins therapy in a plaque of a diabetic patient. In a recent paper from our group (Vicenzini, 2007), we also observed that plaque vascularization can be easily detected with contrast ultrasound imaging in the the fibrous and fibro-fatty tissue and not observed in the calcific nor in the necrotic and haemorrhagic areas, as expression of plaque remodeling. More evidences are now confirming the reliability of this technique (Shah, 2007;Huang, 2008Coll 2010).…”
Section: Ultrasound Contrast Agents For Functional Plaque Imagingmentioning
confidence: 59%
“…Echogenicity was also quantified with Gray Scale Median (GSM) computerized analysis (Biasi, 1999) (ECST, 1995), as percentage of the difference between the original and the residual lumen at the maximum site of stenosis and to the relative increase of blood flow velocities (Sabeti, 2004). Contrast ultrasound investigation was performed, as already described (Vicenzini, 2007), after small repeated bolus injections of SonoVue (Bracco Altana Pharma, Konstanz, Germany) in an antecubital vein (20 Gauge Venflon), followed by saline flushes. After identifying the plaque on longitudinal and transverse scans, and after having obtained the baseline B-mode, Color and Power images of the plaque, the 15 Mhz linear array probe with a mechanical index varying from 0.4 to 1.4 with CPS continuous real-time recording software was used to achieve the best visualization of plaque morphology and vascularization, in the same longitudinal view.…”
Section: Methods Of Ceus Investigationmentioning
confidence: 99%
“…The latter is of great interest in vascular practice due to wide availability, short learning curve and anatomic access due to relative superficial location of carotid artery. Vicenzini et al, studying 23 patients with ACAD, demonstrated that neovascularization is constantly present underneath ulcerated areas rendering the plaque potentially more vulnerable 55 . In addition, the angiogenesis network was identified coming from the adventitia towards the inner layers of the plaque, but this pattern was not detected in hyperechoic plaques with acoustic shadow (calcified) nor in those with advance inflammatory changes, such as hypoechoic necrotic plaques 55 .…”
Section: Surfacementioning
confidence: 99%
“…Vicenzini et al, studying 23 patients with ACAD, demonstrated that neovascularization is constantly present underneath ulcerated areas rendering the plaque potentially more vulnerable 55 . In addition, the angiogenesis network was identified coming from the adventitia towards the inner layers of the plaque, but this pattern was not detected in hyperechoic plaques with acoustic shadow (calcified) nor in those with advance inflammatory changes, such as hypoechoic necrotic plaques 55 . Regression of the adventitial vasa vasorum in a patient upon initiation of treatment with statins was reported suggesting a potential role for treatment monitoring 56 .…”
Section: Surfacementioning
confidence: 99%